2017
DOI: 10.4103/jehp.jehp_181_13
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of nonscholastic abilities and its associated factors among medical students: An exploratory study

Abstract: Background:Nonscholastic abilities among medical students are an important area of concern for the health professionals. Very few studies had been conducted in the past with regard to it.Objective:This study was an exploratory study aimed to assess the nonscholastic abilities among medical students in a medical institution in coastal South India.Materials and Methods:This study assessed three broad domains of nonscholastic abilities namely personal qualities, interpersonal activities, and communication skills … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 9 publications
0
6
1
Order By: Relevance
“…The majority of students had average non-scholastic quality, but the mean score was marginally lesser (17.34) compared to a previous study by Kumar and Sarkar (19.4), which may be due to the inclusion of three classes and larger sample size. [2] The Kumar and Sarkar study analysed these qualities amongst medical students and showed that an overall mean score of non-scholastic abilities was average; and mean personal quality domain score was found to be proportionately lesser than other domains of non-scholastic abilities. [2] Personal qualities, interpersonal activities, and communication skills are very essential to excel in the medical profession.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The majority of students had average non-scholastic quality, but the mean score was marginally lesser (17.34) compared to a previous study by Kumar and Sarkar (19.4), which may be due to the inclusion of three classes and larger sample size. [2] The Kumar and Sarkar study analysed these qualities amongst medical students and showed that an overall mean score of non-scholastic abilities was average; and mean personal quality domain score was found to be proportionately lesser than other domains of non-scholastic abilities. [2] Personal qualities, interpersonal activities, and communication skills are very essential to excel in the medical profession.…”
Section: Discussionmentioning
confidence: 99%
“…This descriptive, cross-sectional study was conducted among medical students of a tertiary care medical institution in Puducherry, India, from July 2018 to September 2018. Using the formula, n = (Z /E) 2 , where Z = 1.96, standard deviation ( ) of the mean non-scholastic quality score as 3.27 [2] and Standard Error as 0.4, the minimum sample size was found to be 257.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations